Post-release monitoring pathway for the deployment of gene drive-modified mosquitoes for malaria control in Africa - Ogoyi, Dorington O.; Njagi, Julia; Tonui, Willy; Dass, Brinda; Quemada, Hector; James, Stephanie (Malaria journal, 2024)
Gene drive-modified mosquitoes (GDMMs) have been promoted as one of the innovative technologies that may control and eliminate malaria and other mosquito-borne diseases. Several products are in early stages of development, targeting either population suppression or population modification of the mosquito vector. However, there is no direct experience of conducting risk assessment for environmental releases and subsequent policies regarding conditions for post-release. This study was carried out to gain additional insights on the possible post-release concerns that may arise, as they may inform future risk assessment and planning for deployment. This study involved desktop reviews on post release monitoring experiences with previously released biological control products. Stakeholder consultations involving online surveys, and face to face workshop with experts from selected African countries from Eastern, Western, and Southern African regions was then carried out to establish post-release monitoring concerns for GDMMs. Review of genetic biocontrol technologies showed only limited lessons from post-release monitoring regimes with a focus largely limited to efficacy. For genetically modified organisms general surveillance and case-specific monitoring is expected in some of the regions. A number of post-release monitoring concerns in relation to the protection goals of human and animal health, biodiversity, and water quality were identified. Based on established- protection goals, several post-release monitoring concerns have been identified. Subject to a rigorous risk assessment process for future GDMMs products, the concerns may then be prioritized for post-release monitoring.